Телемедицина для охраны труда и профилактики профессиональных заболеваний - Завадский, В. А. (НТУ "ХПИ", 2014)
Телемедицина как комплекс организационных, финансовых, правовых, технических и медицинских мероприятий позволяет обеспечить общедоступность медпомощи и единый стандарт качества с помощью использования информационных и телекоммуникационных технологий. Возможности телемедицины позволяют уже на современном уровне своего развития значительно расширить сферу своего применения. Эти возможности основаны на достижениях последних лет в области радиоэлектроники, программирования, информационных технологи и баз данных. Охрана труда и профилактика профессиональных заболеваний органично сочетаются с возможностями телемедицины в едином мощном программно-аппаратном комплексе.

Telemedicine as a set of institutional, financial, legal, technical and medical measures ensures acces-sibility of medical care and a single standard of quality through the use of information and telecommunication technologies. Up-to-date possibilities of telemedicine already allow the development considerably to extend the sphere of the application. These possibilities are based on achievements of recent years in the area of radio electronics, programming, informative technologists and databases. Protection of labour and prevention of professional diseases organically combine with possibilities of telemedicine in a highpowered software and hardware complex. Telemedicine in the near future and will be a key tool for public control of quality and quantity of their health every person positive feedback biotechnology health. The phrase "database of your health", "personal health diary" or "archives of health" will expand and complement the concept of "telemedicine."
Telemedicine for labour protection and praention of professional diseases
Keywords: медицинская помощь; биотехнологии; информационные технологии; программно-аппаратный комплекс; техника средств транспорта; biotechnologies; information technology; prevention of professional diseases; software and hardware complex; telemedicine